Profitability of Islamic Rural Banks in West Sumatra: Analysis of the Third Party Funds and Financial Ratios - Husni Shabri; Anisa Azhari (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
This research examines the problem of profitability in Islamic Rural Bank (BPRS) in West Sumatra Province. The purpose of this study was to analyze Third Party Funds (DPK), Capital Adequacy Ratio (CAR) and Non Performing Financing (NPF) as determinants that affect Return on Asset (ROA) at BPRS in West Sumatra Province through the intervening variable Financing to Deposit Ratio (FDR) for the 2015-2020 period. The research method uses descriptive quantitative approach with statistical path analysis through Sobel test. This study uses secondary data obtained from the financial statements of the BPRS. The results showed that DPK, CAR and FDR had no direct effect on the ROA of BPRS in West Sumatra Province for the 2015-2020 period, only NPF had a direct effect on ROA. While indirectly through intervening variables, DPK and NPF have no effect on ROA, only CAR can be mediated by FDR on ROA. This research contributes to enriching knowledge about Islamic banking and can be used as consideration for entities in increasing the profitability of Islamic Rural Bank by looking at the factors that can affect profitability with FDR as the mediating variable. Penelitian mengkaji tentang masalah profitabilitas pada BPRS di Provinsi Sumatera Barat. Tujuan penelitian ini adalah untuk menganalisis DPK CAR dan NPF sebagai determinan yang mempengaruhi ROA pada BPRS di Provinsi Sumatera Barat melalui intervening variable FDR periode 2015-2020. Metode penelitian menggunakan kuantitatif deskriptif dengan pendekatan statistik path analysis melalui uji sobel. Penelitian ini menggunakan data sekunder yang diperoleh dari laporan keuangan BPRS. Hasil penelitian menunjukan bahwa DPK, CAR dan FDR secara langsung tidak memiliki pengaruh terhadap ROA BPRS di Provinsi Sumatera Barat periode 2015-2020, hanya NPF yang berpengaruh langsung terhadap ROA. Sedangkan secara tidak langsung melalui variable intervening, DPK dan NPF tidak memiliki pengaruh terhadap ROA, hanya CAR yang mampu dimediasi oleh FDR terhadap ROA. Hasil penelitian ini berkontribusi menambah khazanah ilmu pengetahun tentang perbankan syariah dan dapat digunakan sebagai bahan pertimbangan bagi entitas dalam meningkatkan profitabilitas Bank Pembiayaan Rakyat Syariah dengan memperhatikan fator-faktor yang dapat mempengaruhi profitabilitas dengan FDR sebagai variabel mediasi nya.